Pathophysiology of Vascular Remodeling in Hypertension - Nicolás F. Renna; Natalia de las Heras; Roberto M. Miatello (International Journal of Hypertension)
Vascular remodeling refers to alterations in the structure of resistance vessels contributing to elevated systemic vascular resistance in hypertension. We start with some historical aspects, underscoring the importance of Glagov’s contribution. We then move to some basic concepts on the biomechanics of blood vessels and explain the definitions proposed by Mulvany for specific forms of remodeling, especially inward eutrophic and inward hypertrophic. The available evidence for the existence of remodeled resistance vessels in hypertension comes next, with relatively more weight given to human, in comparison with animal data. Mechanisms are discussed. The impact of antihypertensive drug treatment on remodeling is described, again with emphasis on human data. Some details are given on the three mechanisms to date which point to remodeling resistance arteries as an independent predictor of cardiovascular risk in hypertensive patients. We terminate by considering the potential role of remodeling in the pathogenesis of endorgan damage and in the perpetuation of hypertension.